SOSIALISASI OLAHRAGA BOLA TANGAN INDOOR DI KOTA BANDUNG : Penelitian Eksperimen terhadap SMA-SMA di Kota Bandung - Kurniawan, Faris Rizky (2013)
This research entitled "Indoor Handball Sport Socialization in Bandung". The background issue of the research is the less-developed handball sport especially in Senior High School in Bandung. Thus, in order to make handball become more recognized and familiar, socialization of this sport is needed.The population of the research is the student of Senior High School in Bandung and the sample was Labschool UPI Bandung Senior High School, 1 Bandung Senior High School, and 24 Bandung Senior High School. This research aims at finding out students' knowledge about indoor handball sport in both intra and extracurricular program at Senior High School level in Bandung which is considered will give the impact to the development of extracurricular program in schools so that handball will become more popular. The research used experiment method. As the instrument of the research, questionnaires were distributed to the students before and after the socialization. The socialization variables included Knowledge (Information), Recognition, History, and Institutional.The result reveals that there is the improvement on the average value before and after the socialization. The value increases from 197.64 to 217.40. The percentage of each socialization variable also increases. Thus, handball sport should be socialized frequently to the students of Senior High School. Actually, handball sport is given to the students in sport lesson, but the lack of the teachers make students become less-interested to this sport and finally this sport is less-developed. Therefore, the socialization both to the teachers and students is considered really important.